2020
DOI: 10.1002/pa.2330
|View full text |Cite
|
Sign up to set email alerts
|

Examining the factors affecting the use of ICT in teaching in Yemeni schools

Abstract: Owing to the speedy advances in technology, keeping up with such developments and introducing the latest technology in all areas of life are important. In education, many governments have invested in information and communication technology (ICT) to enhance education. However, Yemen remains behind because of many challenges in introducing ICT in education. Thus, this study aims to examine the factors affecting the use of ICT in teaching from the perspective of Yemeni teaching. This study also proposes a model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…ere are a variety of ways that effective use of information technology in the classroom may improve the quality of instruction like ICT (Al-Mamary [49]; Zhang and Zou [50] advancing procedures, providing course materials, mediating discussion, and rearranging pedagogical methods. In addition, this cutting-edge technology has been incorporated into many aspects of language teaching, with generally positive results (see Table 1).…”
Section: Human-computer Interaction In Efl Classroommentioning
confidence: 99%
“…ere are a variety of ways that effective use of information technology in the classroom may improve the quality of instruction like ICT (Al-Mamary [49]; Zhang and Zou [50] advancing procedures, providing course materials, mediating discussion, and rearranging pedagogical methods. In addition, this cutting-edge technology has been incorporated into many aspects of language teaching, with generally positive results (see Table 1).…”
Section: Human-computer Interaction In Efl Classroommentioning
confidence: 99%
“…To assess convergent reliability, factor loadings, composite reliability (CR) and average variance extracted (AVE) were examined [9, [98][99][100][101][102][103][104][105] As specified in Table 2, items' loadings were in the acceptable ranges (0.695and 0.961) [98]. Furthermore, the composite reliability of constructs was above the threshold value of 0.7 [106], Consequently, there are no issues pertaining to internal consistency.…”
Section: Measurement Model Assessmentmentioning
confidence: 99%
“…Al‐Mamary (2020) showed that when using ICTs in education, several problems can occur. Thus, the technical support team should provide technical assistance.…”
Section: Factors Influencing the Use Of Technology In The Education S...mentioning
confidence: 99%
“…Thus, keeping pace with these developments and innovative technologies is necessary for all fields of life. Many governments have started a global investment in technology to improve education (Al‐Mamary, 2020). In the past three decades, information and communication technologies (ICTs) have drastically restructured teaching and learning processes in the context of higher education (Pulkkinen, 2007).…”
Section: Introductionmentioning
confidence: 99%